Direct Liver Invasion from a Gastric Adenocarcinoma as an Initial Presentation of Extranodal Tumor Spread - Mitanshu Shah; Apsara Prasad; Dhyan Rajan; Christopher B. Tan; Mansi Shah; Pooja Raghavan; Paul Mustacchia (Case Reports in Medicine)
Gastric cancer often carries a poor prognosis, with an estimated 740,000 deaths from the malignancy occurring yearly worldwide (Dicken et al., 2005). The mortality of disease is largely dependent on the extent of tumor spread, as gastric cancer has a predilection to metastasize to other visceral secondaries via hematogenous and lymphatic dissemination. Direct invasion of a gastric adenocarcinoma to adjacent organs secondary to gastric wall perforation does occur; however, it is often present in the setting of advanced disease. Rarely does direct tumor invasion to adjacent organs from a gastric adenocarcinoma present as the initial manifestation of extranodal tumor spread. We present a case of a 40-year-old male with direct tumor extension to the liver as an initial presentation of extranodal tumor spread from a gastric adenocarcinoma. Clinicians should be aware of such an occurrence, as treatment modalities in direct liver extension from a gastric adenocarcinoma vary and may be directed towards palliation rather than curative intent.